Membangun Pemahaman Kebencanaan Melalui Focus Group Discussion Kuliah Kerja Luar Negeri - Rio Khoirudin Apriyadi; Sobar Sutisna; Lasmono Lasmono (Universitas Muhammadiyah Mataram, 2022)
Abstract: Focus Group Discussion Overseas Work Lectures (FGD KKLN) is one of the efforts made by the Disaster Management Study Program in increasing students' understanding of disaster science. The study was conducted using a qualitative method with data collection using the Focus Group Discussion technique with the help of the Zoom Meeting application. The stages of activities in the implementation of the KKLN FGD include opening and remarks by the Secretary of the Disaster Management Study Program at The Republic of Indonesia Defense University, prayer readings by officers, presentation by Tohoku University resource persons, a joint discussion between resource persons and students, and the last one is closing. The results of the research and the KKLN FGD activities showed that the implementation of the KKLN FGD activities provided benefits for increasing students' understanding of disaster science, this increase in understanding was evidenced by the results of analysis of student discussions related to non-structural mitigation of earthquake disasters in Japan based on the point of view of experts from Tohoku University.Abstrak: Focus Group Discussion Kuliah Kerja Luar Negeri (FGD KKLN) merupakan salah satu upaya yang dilakukan oleh Program Studi Manajemen Bencana dalam meningkatkan pemahaman mahasiswanya terkait ilmu kebencanaan. Penelitian dilakukan menggunakan metode kualitatif yang pengumpulan datanya menggunakan teknik Focus Group Discussion dengan bantuan aplikasi Zoom Meeting. Tahapan kegiatan pada pelaksanaan FGD KKLN meliputi pembukaan dan sambutan oleh Sekretaris Program Studi Manajemen Bencana Universitas Pertahanan Republik Indonesia, pembacaan doa oleh petugas, presentasi oleh Narasumber Universitas Tohoku, diskusi bersama antara narasumber dan mahasiswa, dan yang terakhir adalah penutup. Hasil penelitian dan kegiatan FGD KKLN menunjukkan bahwa pelaksanaan kegiatan FGD KKLN memberikan manfaat peningkatan pemahaman mahasiswa terkait ilmu kebencanaan, peningkatan pemahaman tersebut dibuktikan dengan hasil analisis diskusi mahasiswa terkait mitigasi nonstruktural bencana gempa bumi di Jepang berdasarkan sudut pandang pakar dari Universitas Tohoku.